Perlindungan Perempuan dan Anak dalam Hukum Keluarga Islam Perspektif Maqashid Syariah Index - Abdurrahman Hakim; Asep Nuhdi; Shofura Syahidah; Abdul Husenudin (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine the legitimacy of strengthening the protection of women and children within Islamic family law through the perspective of the Maqashid Sharia Index as a normative and socio-legal evaluative framework. The study is motivated by the increasing complexity of issues affecting women and children, including domestic violence, child marriage, gender-based discrimination, and other forms of vulnerability that require a more comprehensive and welfare-oriented legal protection system. This research employs a qualitative approach using a library research method. Data were collected through documentation of primary sources, including legislation, Islamic family law literature, and classical and contemporary works on maqashid al-shariah, supported by secondary sources such as scholarly articles, research reports, and policy documents. Data were analyzed using content analysis and normative interpretation techniques. The findings reveal that strengthening the protection of women and children possesses strong legitimacy within Islamic family law because it aligns with the fundamental objectives of maqashid al-shariah, namely the protection of religion (hifz al-din), life (hifz al-nafs), intellect (hifz al-'aql), lineage (hifz al-nasl), wealth (hifz al-mal), and human dignity. Furthermore, the Maqashid Sharia Index provides an analytical framework for assessing the effectiveness of family law policies and practices in promoting justice, welfare, and the protection of vulnerable groups. This study highlights the importance of reformulating Islamic family law policies that are more responsive to the protection of women and children and suggests further research on developing empirical indicators of the Maqashid Sharia Index within the implementation of family law in Indonesia.